Determinacion de la produccion de jalea real en colmenas de recria de diferentes dimensiones - Ballesteros, H.H.=700 1 Vasquez, R.E.
(Es, En)
Ilus., 8 ref.
Keywords: APICULTURA; JALEA REAL; COLMENA; ZONA TROPICAL; COLOMBIA; RECRIA; REVISTA CORPOICA